Production and Use of ICT A Sectoral Perspective on Productivity Growth in the OECD Area - Pilat, Dirk (OECD Publishing, 2003)
This paper examines the roles of the ICT-producing sector and of key ICT-using industries in overall productivity growth in OECD countries. The ICT manufacturing sector, in particular, has been characterised by very high rates of productivity growth in many countries and provides a large contribution to labour productivity growth in Finland, Ireland and Korea. In a few countries, notably the United States and Australia, certain ICT-using services have also experienced an above-average pick-up in productivity growth in the second half of the 1990s. Further structural reform may be needed before ICT use will also show up in the productivity statistics of other OECD countries. Differences in the measurement of productivity in ICT-producing and -using industries across countries complicate the cross-country analysis
Keywords: Economics